Static balance in the standing shooting posture is associated with balance in biathlon standing shooting - Köykkä, M.; Laaksonen, M. S.; Ruotsalainen, K.; Ohtonen, O.; Linnamo, V. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Postural balance is one of the major contributing factors in successful biathlon standing shooting 1. It has traditionally been assessed by measuring center of pressure (COP) movement with force plates in a test where the biathlete shoots multiple 5-shot sets 2. This study investigated the associations of balance in biathlon standing shooting with balance in a holding task to explore the importance of static balance control in biathlon standing shooting.